(untitled) (Applied Biological Research, 2016)
The present study was aimed to assess the performance of neonatal buffalo calves based on haematological and biochemical profile upon supplementation of Emblica officinalis and Tinospora cordifolia, well known anti-anaemic, adaptogenic and anti-stressor herbs. Twelve calves aged 14 d were randomly divided into 2 groups of 6 each. One group was maintained as control and other group supplemented with a combination of dry powder of E. officinalis and T. cordifolia (2:1) @ 450 mg kg-1 body weight once a day orally for 28 days. Blood samples were collected aseptically from control and experimental animals on 28th and 42nd day age of calves from jugular vein. The treatment group showed significantly higher (p<0.05) total erythrocyte count, packed cell volume and haemoglobin concentration in blood. Total leukocyte count and L:N was significantly higher in treatment group than control group. No significant changes were observed in blood glucose, total protein, serum cholesterol and serum triglycerides during the experimental period.